1997
DOI: 10.1159/000289128
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Assessment of Patients with Idiopathic Pruritus ani

Abstract: Background: The purpose of this study was to compare psychological profiles in 17 patients suffering from idiopathic pruritus ani with a control group of 28 patients showing secondary pruritus ani. Methods: The two groups completed the Mini-Mult personality test and results were compared using χ2 test and analysis of variance. Results: The mean hypomania and depression scale scores were greater and smaller respectively in the idiopathic pruritus ani group. Nevertheless, the percentage of abnormal ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…Laurent et al showed that the mean hypomania and depression scale scores were greater and smaller respectively in the idiopathic perianal pruritus patients. 10 In two of our patients, depression was diagnosed after psychiatric consultation.…”
Section: Discussionmentioning
confidence: 89%
“…Laurent et al showed that the mean hypomania and depression scale scores were greater and smaller respectively in the idiopathic perianal pruritus patients. 10 In two of our patients, depression was diagnosed after psychiatric consultation.…”
Section: Discussionmentioning
confidence: 89%
“…Psychological profiles of patients with pruritus ani are not different from those of the general population [9].…”
Section: Discussionmentioning
confidence: 81%
“…Literature reports the use of clomipramine, fluoxetine and fluvoxamine in this compulsive behavior. Often, psychogenic pruritus has been associated with an inability to manage aggressive tendencies, characterological armoring with congestion of aggressive impulses [12], though this is not completely agreed upon [23]. Even if it seems arbitrary to assess a personality pattern in patients with psychogenic pruritus, we believe that the choice of psychopharmacological agents must be conditioned by personality traits according to a dimensional approach.…”
Section: Discussionmentioning
confidence: 99%